STUDI KANDUNGAN KADAR LOGAM BERAT (TEMBAGA, ZINK, TIMBAL, KROMIUM DAN KADMIUM) DALAM AIR DI SUNGAI LALANG, DESA SUKA MAJU, KABUPATEN BATU BARA, PROVINSI SUMATRA UTARA - Purba, Evan Gomgom Tua; Ria Retno; Ewin Handoco (Journal of Research and Publication Innovation, 2024)
Rivers are naturally formed channels on the earth's surface that collect and channel rainwater from high areas to lower areas and eventually end up in lakes or the sea. Heavy metals are metals that have a specific gravity greater than 5 g/cm3. Basically, these heavy metals pollute soil, water, and air. Heavy metals that accumulate in the body are one of the causes of degenerative diseases, especially cancer. The purpose of this study was to determine the levels of heavy metals based on the parameters of Copper and Zinc in Lalang River, Suka Maju Village, Batu Bara. Analyze the data from the test results of heavy metal levels based on the parameters of copper and zinc obtained, then compare with the water quality standards set in Appendix IV of PPRI Number 22 of 2021 concerning river water quality standards and the like. The results of heavy metal measurements of Copper (Cu) and Zinc (Zn) conducted at the Medan Baristand Laboratory, it can be concluded that the third research station still meets the river water quality standards according to PPRI No. 22 of 2021 class II. In the parameters of temperature, DO, pH and salinity still meet the air quality standards according to PPRI No. 22 of 2021 class II.